2007 IEEE International Symposium on Information Theory 2007
DOI: 10.1109/isit.2007.4557282
|View full text |Cite
|
Sign up to set email alerts
|

Random Linear Network Coding: A free cipher?

Abstract: THIS PAPER IS ELIGIBLE FOR THE STU-DENT PAPER AWARD" We consider the level of information security provided by random linear network coding in network scenarios in which all nodes comply with the communication protocols yet are assumed to be potential eavesdroppers (i.e. "nice but curious"). For this setup, which differs from wiretapping scenarios considered previously, we develop a natural algebraic security criterion, and prove several of its key properties. A preliminary analysis of the impact of network to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(78 citation statements)
references
References 10 publications
(15 reference statements)
0
78
0
Order By: Relevance
“…In practice, random linear coding has been widely used in the literature [15,22], because of the simplicity of the coding scheme. With random linear coding, random linear combinations of the packets can be forwarded by a node, which the node received previously, to outgoing edges.…”
Section: Reliable Communication Using Random Linear Network Codingmentioning
confidence: 99%
“…In practice, random linear coding has been widely used in the literature [15,22], because of the simplicity of the coding scheme. With random linear coding, random linear combinations of the packets can be forwarded by a node, which the node received previously, to outgoing edges.…”
Section: Reliable Communication Using Random Linear Network Codingmentioning
confidence: 99%
“…The first kind is mainly for resisting internal attackers, i.e., preventing intermediate nodes from acquiring source private data by using the information flowing across them [3][4][5] . Lima et al 3 showed that network coding could offer information-theoretic security against internal attackers with high probability, if the source disseminates encoded blocks of data by using multiple paths and the size of the codeword field goes to infinity. 4 proposed a secure multi-path network coding schemes for WSNs.…”
Section: Related Workmentioning
confidence: 99%
“…Some SNC protocols are designed for preserving private data from being obtained by any intermediate node that is not an intended recipient [3][4][5] . Some are for resisting eavesdropping attacks [6][7][8] , and the others are for resisting pollution attacks [9][10][11][12][13][14] , both of which are external attacks.…”
Section: Introductionmentioning
confidence: 99%
“…The work in [15] derives bounds for the probability of decoding an individual symbol in a network where Random Linear Network Coding (RLNC, i.e., random mixings of packets at the intermediate nodes of the network) is used. It is shown that RLNC increases the security for a threat model in which the intermediate nodes comply with the protocol however may try to decode as much as possible.…”
Section: B Comparison With Competing Coding Techniquesmentioning
confidence: 99%